Overcrowding and sense of home in the Canadian Arctic. Issue 2 (7th February 2020) - Perreault, Karine; Riva, Mylène; Dufresne, Philippe; Fletcher, Christopher
Abstract: This study examines the relationship between living in overcrowded conditions and sense of home among 289 Inuit, the Indigenous population living in the Canadian Arctic. This study was conducted in Nunavut and Nunavik, two of the four Inuit regions in Canada, where the prevalence of overcrowding is six times the national average. Sense of home was derived from the conceptual notion of ontological security, where home is defined as a symbolic place for making claims of cultural identity and belonging. Sense of home was operationalized according to participants' perception of their home in relation to space, identity, control, privacy, satisfaction, relationships, location, and security. Overcrowding was negatively associated with sense of home. In overcrowded dwellings, fewer women reported positive perceptions of their house with regards to sufficient space, feeling of identity, satisfaction and domestic relationships. Relational and cultural aspects of housing resonate with sense of home and may be particularly interesting to examine as potential mechanisms leading to individual and community wellbeing.